2022
DOI: 10.1038/s41390-022-02219-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap inhibition improves survival in neonatal mouse infectious peritonitis

Abstract: Background Treatment of neonatal peritonitis and sepsis is challenging. Following infection, neutrophils elaborate neutrophil extracellular traps (NETs)—extracellular lattices of decondensed chromatin decorated with antimicrobial proteins. NETs, however, can augment pathogenic inflammation causing collateral damage. We hypothesized that NET inhibition would improve survival in experimental neonatal infectious peritonitis. Methods We induced peritonitis in 7 to 10-day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Importantly, our data highlight the potential role of nNIF and NET inhibition as a new treatment approach in the early phase of infection in polymicrobial sepsis in vivo. This study corroborates findings from our recent study in which nNIF treatment before or after initiation of peritonitis inhibited NET formation in a murine model of neonatal polymicrobial peritonitis and endotoxemia resulting from intraperitoneal LPS injection ( 27 ). In the current study, we go a step further and investigate nNIF as an adjuvant therapy in combination with a broad-spectrum antibiotic for the treatment of septic mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, our data highlight the potential role of nNIF and NET inhibition as a new treatment approach in the early phase of infection in polymicrobial sepsis in vivo. This study corroborates findings from our recent study in which nNIF treatment before or after initiation of peritonitis inhibited NET formation in a murine model of neonatal polymicrobial peritonitis and endotoxemia resulting from intraperitoneal LPS injection ( 27 ). In the current study, we go a step further and investigate nNIF as an adjuvant therapy in combination with a broad-spectrum antibiotic for the treatment of septic mice.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by the fact that nNIF-treated mice displayed a rapid and considerable increase of CFU counts at the site of infection in the peritoneal fluid as well as in the plasma as opposed to the bacteria being removed from circulation by NETs. Of note, we previously demonstrated that neutrophils exposed to nNIF still maintain their ability to generate reactive-oxygen species and phagocytize E. coli bioparticles ( 12 , 27 ). Considering all the data together, we propose that NET inhibition with nNIF effectively blocks NET formation leading to increased bacterial CFUs due to lack of NET-mediated extracellular microbial killing and decreased neutrophil activation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NETS have been shown to have both protective and detrimental features in sepsis, the latter by induction of thrombosis and multiple organ failure. Yet many key questions regarding their exact role in the pathophysiology of (pediatric) sepsis remain unanswered [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A1ATm358, another placental-related modulatory factor found in the perinatal milieu, is no longer active in neonates after birth [ 32 ]. Only recently has it been shown that the group of NET inhibitors improves survival in experimental neonatal infectious peritonitis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%